A Comparative Analysis of Life Cycle Costs and Emissions in Mae Sariang’s Microgrid Energy Scenarios - Yathip, Bancha; Usapein, Parnuwat; Madtharad, Chakphed; Jirawongnusorn, Sirichai (International Journal of Energy Economics and Policy, 2025)
This study evaluates the life cycle costs, net present value (NPV), and greenhouse gas (GHG) emissions of three energy scenarios for the Mae Sariang microgrid system to assess the economic and environmental impacts of different energy sources. The reliance on renewable energy has become increasingly vital in addressing energy sustainability and reducing carbon footprints. The analysis reveals that Scenario I, primarily utilizing solar energy, achieved the lowest life cycle cost per kilowatt-hour (kWh) at 6.18 and the highest NPV of 226,583,036 baht, while also producing the fewest GHG emissions at 21,239 kgCO₂e/year. In contrast, Scenario II, dependent on grid electricity, incurred the highest costs and emissions at 25,180 kgCO₂e/year, reflecting its reliance on higher-carbon sources. Scenario III, which incorporates diesel generation, demonstrated moderate emissions at 22,240 kgCO₂e/year but resulted in a negative NPV of -2,690,330 baht due to high fuel expenses. The findings highlight that prioritizing renewable energy sources not only enhances financial viability but also minimizes environmental impact. Therefore, the study concludes that adopting a renewable-focused approach in microgrid systems offers substantial economic and ecological benefits. Policy recommendations include incentivizing renewable energy integration, promoting energy efficiency measures, and developing supportive frameworks to reduce reliance on high-carbon electricity, ultimately enhancing the feasibility and sustainability of energy systems.